GLOBALISASI EKONOMI DAN MONETER SYARIAH DI REGIONAL ASEAN: PERSPEKTIF POLITIK EKONOMI ISLAM - Desi Yuniarti (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
Economic globalization leads to economic liberalization and privatization (privatization). This is a consequence of the expansion of capital or capital spread by developed countries throughout the country. Thus, globalization will reform national structures and policies to be implemented with global interests.